The evolution of the southern Namibian Karoo-aged basins: implications from detrital zircon geochronologic and geochemistry data. Issue 14 (22nd September 2021) - Zieger, J.; Stutzriemer, M.; Hofmann, M.; Gärtner, A.; Gerdes, A.; Marko, L.; Linnemann, U.
ABSTRACT: Detrital U-Pb zircon age dating and grain morphometrics were used for provenance and maximum deposition age determination for the Lower Permian Dwyka and Middle to Upper Permian Ecca groups of southern Namibia's Aranos and Karasburg basins. Thirteen sedimentary samples and one ash fall sample were analysed using laser ablation – single collector – inductively coupled plasma – mass spectrometry (LA-ICP-MS). The results reveal prominent Cambrian to Neoproterozoic (500–750 Ma), a Lower Neoproterozoic to Mesoproterozoic (950–1300 Ma), and Upper Palaeoproterozoic (1775–1950 Ma) detrital zircon age populations. Multiple evidence (e.g. roundness of investigated zircon grains and Ɛ Hf values) suggest the zircon populations are part of a Gondwana-wide recycling system, where basins act as intermediate reservoirs and eventual dispersers. Classic source to sink dynamics do not apply. A Permian age population (ca. 260–296 Ma) consisting of typically euhedral zircon grains is assumed to be derived directly from protolith rocks. Because no felsic Permian rocks are exposed in the southern African region, these findings suggest a significant input by ash fall from an unknown source, which may be linked to the southern Gondwanan arc volcanism during Permian times. The results reveal a ca. 36 Ma duration of the evolution of the Karasburg Basin and a shorter ca. 30 Ma lasting evolution of the Aranos Basin. The stratigraphic oldest datable unit is an ash bed of the Ganigobis Shale Member of the Zwartbas Fm (Dwyka Group) which gave a maximum deposition age of ca. 296 Ma, whereas the Aussenkjer Fm represents the uppermost Namibian Karoo-aged strata with a maximum age of deposition of ca. 260 Ma.